MOBILE-BASED E-COMPLAINT TECHNOLOGY FOR THE GOVERNMENT OF BANDAR LAMPUNG - Amnah Amnah; Hariyanto Wibowo (Proceeding International Conference on Information Technology and Business, 2020)
Bandar Lampung is the capital city of Lampung Province carrying out a lot of public infrastructure development. This development must have maintenance in the field of infrastructure. The problem statement of this study was seen on the damaged infrastructure so that it needed improvement in order that people were able to submit the complaints or aspirations on the recent infrastructure. The objective of this study wass to design the mobile-based e-complaint technology for the Government of Bandar Lampung. This E-Complaint technology was developed through the Waterfall method containing Literature Study, Observation, Interview, Documentation, UML, Waterfall Formation, and Coding Writing. This software wass tested with Black-box testing in order to obtain the accurate results originated from the users’ need. The last step was socializing this application to the public so that people understood the way to use and know the function of this software. The result of this study was in the form of A Mobile-Based E-Complaint Technology Application for the Government of Bandar Lampung. This application facilitated the people of Bandar Lampung to report all their complaints or aspirations directly to the Government of Bandar Lampung. Keywords: E-Complaint, Mobile-Based Application